2008
DOI: 10.1016/j.jacc.2008.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Is Associated With Greater Thoracic Aortic Size

Abstract: Obstructive sleep apnea (OSA), characterized by partial or complete occlusion of the pharynx during sleep, results in persistent inspiratory effort and interruption of airflow. During each episode of apnea, OSA patients develop increased transmural pressure in the aortic wall. Accordingly, to test the hypothesis that the presence of OSA would be associated with greater thoracic aortic size, we prospectively assessed 150 consecutive patients, newly referred to the sleep clinic in our institution, in a crosssect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 5 publications
(6 reference statements)
1
35
1
1
Order By: Relevance
“…Most of the studies investigated the association between OSA and the aortic root diameter [44][45][46][47][48][49][50][51][52]. Six cross-sectional studies investigating patients referred for a sleep evaluation reported a positive association between the aortic root diameter and parameters of OSA severity (either AHI or oxygen desaturation index (ODI)) [45,[48][49][50][51][52]. Notably, one study found an association with AHI in rapid eye movement sleep only where the severity of OSA becomes greater, partly due to a decreased respiratory muscle tone [52].…”
Section: General Populationmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies investigated the association between OSA and the aortic root diameter [44][45][46][47][48][49][50][51][52]. Six cross-sectional studies investigating patients referred for a sleep evaluation reported a positive association between the aortic root diameter and parameters of OSA severity (either AHI or oxygen desaturation index (ODI)) [45,[48][49][50][51][52]. Notably, one study found an association with AHI in rapid eye movement sleep only where the severity of OSA becomes greater, partly due to a decreased respiratory muscle tone [52].…”
Section: General Populationmentioning
confidence: 99%
“…These variations include, for example, the facts that the treatment status of OSA was not taken into account [46], common diagnostic criteria have not been consistently applied [45,47,51] and some studies lacked a control group [46,58,60]. In studies assessing the thoracic aorta there is also a high between-study variation in methodological aspects, as studies do not use consistent anatomic landmarks [41,[44][45][46][47][49][50][51]. When considering conflicting results among thoracic and abdominal diameters measured at different anatomic landmarks and the fact that, even in a single study, aortic diameters at different landmarks were distinctly affected by OSA, one may hypothesise that the aetiological significance of OSA may vary along the aorta [53].…”
Section: Current Limitations Of Published Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the future, examination of whether treatment of OSA is involved in aortic diameter diminution is necessary. In connection, Serizawa, et al recently suggested that OSA may contribute to increased thoracic aortic size through mechanical stress on the aortic wall due to repeated episodes of apnea and hypopnea, independently of systemic hypertension 11) . Moreover, G. Sampol, et al, showed that patients with aortic dissection (n 19) had a significantly larger AHI than patients with matched age, sex, BMI, blood pressure and neck circumference (n 19), and that the number of aortic dissection patients with severe OSA, with an AHI greater than 30/hr, was significantly larger than that of the control group 1) .…”
Section: Discussionmentioning
confidence: 99%